Strengthening Cross Sectors for Against Hypertension Case Study Posbindu PTM - Arifuddin, Muh. Asrul Taufiq (Institute of Computer Science (IOCS), 2025)
The human lifestyle is caused by urbanization, modernization, and globalization which causes non-communicable diseases (PTM). One form of Community-Based Health Efforts (UKBM) that was newly developed by the government was in accordance with WHO recommendations, namely the Integrated Non- Communicable Disease Development Post (Posbindu PTM). This type of research is qualitative with a case study design and descriptive. The research subjects were 22 informants. Data collection is carried out data through in-depth interviews, observations, and document searches. To find out the validity of the data using the source triangulation method. Data analysis was done qualitatively by content analysis method. The results of the study, namely the dissemination of Posbindu PTM in the work area of Tinggimoncong Community Health Center in 2018, the head of the puskesmas invited across sectors, Tinggimoncong district cadres, and principals to attend the Posbindu PTM socialization activities. In the process of implementing Posbindu PTM advocacy in the work area of Tinggimoncong Community Health Center in 2018, there was a strengthening of the local government to the cadres by issuing SK Cadres issued by the sub-district head, village head / village. The conclusion is that the implementation of the Posbindu PTM in the Working Area of Tinggimoncong Health Center has gone as expected.